A law and development analysis of parallel law systems within the natural resources sector in Africa - (:unkn) unknown (My University, 2018)
The normative position of this dissertation is that there is a constraint of the law with regards to the mining regime of resource rich countries in Africa. This has resulted in the creation of a pluralist system of law will continue to thrive in developing countries as a result of the historical context which most of these countries derive. However, having a mixed system comprising of a formal and informal legal regime does not necessarily equate a disadvantage. The problem arises when there is a reluctance in accepting one of these systems. This is the case currently with the informal regime which exists mostly as an unrecognized and therefore illegitimate system of law. Yet, evidence from this dissertation shows the advantages which informal rules and norms can offer to a country’s legal regime. In this regard, it is therefore reasonable to suggest that something ought to be done with this system as opposed to its continued marginalization in the shadows of the formal regime. This dissertation therefore proposes the formalization of selected attributes of the informal system which govern the natural resources sector of resouce rich countries in Africa. Moreover, the formalization envisioned in the mining sector, makes no attempt to codify laws and is in alignment with a local to international approach to law making. In this regard, the aim for formalization, as proposed by this dissertation, is in finding possible solutions for bridging the hiatus between the formal and informal regime which currently work in parallel with each other within the mining space. This is in hopes that the synchronizing of these two sets of laws would facilitate the flourishing of economic and human/social development based on the mining sector.
Keywords: African Research